2018
DOI: 10.1016/j.bmcl.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Histidine N(τ)-cyclized macrocycles as a new genre of polo-like kinase 1 polo-box domain-binding inhibitors

Abstract: Transition toward peptide mimetics of reduced size is an important objective of peptide macrocyclization. We have previously shown that PLHSpT (2a) (where H indicates the presence of a -(CH)Ph group at the N(π) position and pT indicates phosphothreonine) is an extremely high affinity ligand of the polo-like kinase 1 (Plk1) polo-box domain (PBD). Herein we report that C-terminal macrocyclization of 2a employing N(π),N(τ)-bis-alkylated His residues as ring junctions can be achieved in a very direct fashion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The complex was formed and crystals were grown using the same methods and under similar conditions to the complex with a related macrocycle. 58 Briefly, frozen PBD stock at 37 mg mL −1 was thawed and diluted to 10 mg mL −1 . A stock solution of the macrocycle at 100 mM in DMSO was added directly to the diluted protein to a final concentration of 1 mM, then 4 M ammonium acetate was added to a final 0.4 M concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The complex was formed and crystals were grown using the same methods and under similar conditions to the complex with a related macrocycle. 58 Briefly, frozen PBD stock at 37 mg mL −1 was thawed and diluted to 10 mg mL −1 . A stock solution of the macrocycle at 100 mM in DMSO was added directly to the diluted protein to a final concentration of 1 mM, then 4 M ammonium acetate was added to a final 0.4 M concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Hymel et al [ 19 ] reported the synthesis of tripeptide ligands with decreased molecular weight 11 – 14 ( Figure 4 ). This was conducted by C -terminal macrocyclisation, employing N(π),N(τ)-bis-alkylated residues as ring junctions and showing improved target selectivity for the polo-box domain of polo-like kinase 1 (Plk1 PBD) versus the PBDs of Plk2 and Plk3.…”
Section: Synthesis Of Imidazolic Macrocyclesmentioning
confidence: 99%
“…Among them, GW843682 has the closest IC 50 level toward PLK3 compared to that of PLK1 (9.1 nM for PLK3 vs. 2.2 nM for PLK1) ( Murugan et al, 2011 ; Liu, 2015 ). Attempts to enhance the specificity toward PLKs over other kinases or PLK1 over other PLKs have been made to inhibit its PBD using small molecules, phosphopeptides, or using siRNA ( Kumar and Kim, 2015 ; Hymel et al, 2018 ; Alverez et al, 2020 ). For instance, small chemicals Poloxin and poloxipan inhibit the polo box of PLKs with the IC 50 ranging from 1.17 μM to 53.9 μM toward PLK 1/2/3.…”
Section: Potential Of Targeting the Siah2-hif-1 Axis And Its Kinase Rmentioning
confidence: 99%